FAKTOR – FAKTOR YANG MEMPENGARUHI STATUS GIZI KURANG PADA BALITA DI DESA SARIMAHI KECAMATAN CIPARAY KABUPATEN BANDUNG - Sumiati, Nenden Sum; Rosita, Rosita; Herawati, Yanti; Aminudin, Sri hennyati (Jurnal Sehat Masada, 2025)
The problem of malnutrition is still a major concern in various countries, especially in the toddler group. There are several indirect factors that influence malnutrition in toddlers, including knowledge, education, employment, pregnancy spacing and family income. This research aims to determine the factors that influence the malnutrition status of children under five in Sarimahi village in 2024. The research design used correlative analytics with a point time approach. The population and sample for this study were all 56 babies and toddlers in the working area of ​​the Ciparay Community Health Center, using a total sampling technique. The data used is primary data using a questionnaire. The data analysis used was univariate and bivariate using the Chi square statistical test. The research results showed that the mother's level of knowledge was sufficient, she had low education, did not work, had a pregnancy interval of > 2 years, had a high income and the toddler was malnourished. The results of the bivariate analysis showed a relationship between knowledge (pvalue 0.004), education (pvalue 0.001) and pregnancy interval (pvalue 0.000) with malnutrition status in toddlers and no relationship between employment (pvalue 1.000) and family income (pvalue 0.310). The conclusion is that there is a relationship between knowledge, education, distance between pregnancies and malnutrition status in toddlers and there is no relationship between employment and family income and undernutrition status in toddlers. It is recommended that the community health center or other health facilities create an interactive communication strategy for mothers and health workers as an ongoing activity in preventing malnutrition